The Influence of Parental Knowledge and Experience on Behavioral Management in Child Rearing - Maria Prieska Putri Panglipur Ati; Ifa Pannya Sakti (STIKep PPNI Jawa Barat, 2026)
Background: Children’s emotional reactions, such as fear or resistance, are strongly influenced by how parents manage their behavior during medical procedures. Effective behavioral management which means parenting practices in managing children’s behavior, plays a crucial role in helping children face medical procedures calmly and cooperatively. Various factors may affect implementation of behavioral management, including knowledge and experience. Objective: This study aimed to examine the association of parents’ knowledge and experience on the implementation of behavioral management in parenting. Methods: This study employed a quantitative, non-experimental design. The population consisted of parents whose children received health examinations at the Pediatric Outpatient Clinic, with a total of 70 participants selected using accidental sampling. Data were analyzed using ordinal logistic regression. Results: Respondents with poor knowledge had a 68% lower likelihood of demonstrating better behavior management compared with those with good knowledge (OR = 0.32; 95% CI: 0.10–0.96; p = 0.05), while moderate knowledge showed a similar but statistically non-significant trend (OR = 0.42; p = 0.09). Respondents with poor experience had a 70% lower likelihood of exhibiting better behavior management (OR = 0.30; 95% CI: 0.09–1.00; p = 0.05), whereas moderate experience was not significantly associated with behavior management (OR = 1.18; p = 0.73). Conclusion: Parents are expected to apply behavioral management strategies in clinical setting based on knowledge and experience to reduce fear and anxiety in children, such as preparatory communication, distraction techniques, play therapy and collaboration with health care staff.